1994
DOI: 10.1002/mus.880171208
|View full text |Cite
|
Sign up to set email alerts
|

Passive transfer of seronegative myasthenia gravis to mice

Abstract: Muscle weakness in myasthenia gravis is due to autoantibody-induced loss of functional acetylcholine receptors (AChR). About 15% of myasthenia gravis patients, however, do not have detectable anti-AChR antibodies. To investigate the effect of their plasma immunoglobulins on neuromuscular transmission, mice were injected with plasma (and in some cases purified immunoglobulin G (IgG)) from 7 "seronegative" myasthenia gravis (SMG) patients, and neuromuscular transmission parameters were examined. When injected fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
44
0
4

Year Published

1999
1999
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 172 publications
(49 citation statements)
references
References 36 publications
1
44
0
4
Order By: Relevance
“…MuSK is essential for the development of the NMJ [51] but its role in adult muscle is less clear although it probably plays an important role in maintaining the structure of the postsynaptic membrane. [52] MuSK-MG often presents with ocular involvement, but frequently evolves to include severe bulbar and facial weakness, sometimes with marked muscle atrophy in these muscles.…”
Section: Myasthenia Gravis With Muscle-speciþ C Kinase Antibodiesmentioning
confidence: 99%
“…MuSK is essential for the development of the NMJ [51] but its role in adult muscle is less clear although it probably plays an important role in maintaining the structure of the postsynaptic membrane. [52] MuSK-MG often presents with ocular involvement, but frequently evolves to include severe bulbar and facial weakness, sometimes with marked muscle atrophy in these muscles.…”
Section: Myasthenia Gravis With Muscle-speciþ C Kinase Antibodiesmentioning
confidence: 99%
“…Blood was collected, and serum was prepared at 0. 25,6,24,30,48,72,96,144,192, and 240 h after the injection. A specific ELISA was used to determine 1G3 and mIgG1 serum concentration as described in Materials and Methods.…”
Section: High Affinity Binding Of 1g3 To Rat Fcrn and Competition Formentioning
confidence: 99%
“…Up to 90% of MG patients have detectable Abs against AChR, whereas ϳ10 -15% of the patients are negative for anti-AChR Abs (seronegative MG; SNMG) (3,4). However, Igs from sera of SNMG patients bind to muscle cells that do not express AChR (5), and they induce reductions in miniature endplate potential amplitudes upon passive transfer to mice (6). Moreover, it has been shown that 47-70% of SNMG patients have serum IgG autoantibodies against the muscle-specific receptor tyrosine kinase.…”
mentioning
confidence: 99%
“…Les études menées dans les années 90 ont permis de confirmer que le facteur humoral est bien à l'origine de la myasthénie séronégative. Il faut notamment citer ici l'effet bénéfique des échanges plasmatiques dans ce groupe de patients ainsi que la présence de troubles de la transmission neuromusculaire chez la souris recevant du sérum de patients myasthéniques séronégatifs [6]. Deux hypothèses ont été émises pour expliquer ce phénomène de « séronégativité » : 1/ que la technique de radioimmunoprécipita-tion (RIPA) pourrait ne pas être suffisamment sensible pour détecter les anticorps anti-RACh à faible concentration et 2/ qu'il existerait peut-être d'autres anticorps impliqués dans la pathophysiologie de la myasthénie auto-immune.…”
Section: « Nouveaux Anticorps » : Physiopathologie Et Aspects Cliniquesunclassified